Effectiveness of Tai Chi therapy on sleep quality among elderly residing at selected old age homes - DR. LISY JOSEPH,; DR. T.V.RAMAKRISHNAN, (International Journal of Pharma and Bio Sciences, 2019)
Ageing is a universal phenomenon. As a result of many socio-demographic changes, older adults at times are forced to shift from their own place of residence to some institutions named as old age homes. Being relocated to an old age home can result in sleep disturbances among elders. Sleep is vital for human being because it helps body to rest, repair and maintain proper body's circadian rhythm. This study is aimed to test the effects of Tai Chi therapy in improving sleep quality among elderly living in old age homes. Tai C hi, which originated in ancient China, is a Chinese conditioning exercise well known for its graceful movement, which combines deep diaphragmatic breathing with continuous body motions to achieve a harmonious balance between body and mind. A quasi-experimental pretest-and-posttest design was used, in which the selected elderly were taught Tai Chi therapy and were made to practice it as one hour session twice weekly for 12 weeks under direct supervision of the researcher. Following this they were to practice the same as one hour session twice weekly until the end of 36 weeks on their own. A convenience sample of 150 elderly residents of old age homes were divided randomly into a Tai Chi therapy group (n=75) and control group (n=75) based on residence location. Subjects with severe depression, severe sensory deficits and those who had an inability to perform Tai Chi therapy as they were bedridden or were using supportive devices for mobility and subjects who were not willing to participate were excluded from the study. A total of 139 participants completed the study. Sleep quality of the subjects were screened using Pittsburgh Sleep Quality Index (PSQI), which is an 18 item, self-rated questionnaire eliciting sleep quality. The outcome measures of sleep quality were examined at baseline, at the 12th week, 24th week and at the 36th week of the study. After 9 months of performing Tai Chi therapy, participants’ overall sleep quality had significantly improved, whereas sleep disturbances and daytime dysfunction had decreased significantly (p < .05). Thus Tai Chi therapy can be incorporated as an activity program in old age homes or in other long-term care facilities to improve sleep quality among elderly.